Antibody Against N‐terminal Domain of Phospholipid Scramblase 1 Induces Apoptosis in Colorectal Cancer Cells Through the Intrinsic Apoptotic Pathway. (7th June 2014) - Chen, Chun‐Yu; Chen, Jinn‐Shiun; Chou, Yeh‐Pin; Kuo, Yung‐Bin; Fan, Chung‐Wei; Chan, Err‐Cheng
<x xml:space="preserve">Abstract</x> Phospholipid scramblase 1 involve in biological processes including phospholipid movement, proliferation, and apoptosis. Treatment with an antiphospholipid scramblase 1 antibody (NP1) has been demonstrated to inhibit cell proliferation in colorectal cancer. This study aimed to explore the role of NP1 treatment in the apoptosis of colorectal cancer cells. Results showed that NP1 treatment significantly increases the apoptosis of colorectal cancer cells via the activation of caspase 8, caspase 9, and caspase 3. Moreover, pretreatment with a caspase 8 inhibitor did not fully prevent the apoptotic effects of NP1. Taken together, these data indicate NP1 induces cell apoptosis primary through the intrinsic apoptotic pathway. NP1 may serve as a potential therapeutic agent.